Seeking or risk: mental health symptoms and associated behaviors in college student-athletes - Davis, Samuel R., author; Prince, Mark A., advisor; Conner, Bradley T., committee member; Butki, Brian, committee member; Swaim, Randall, committee member (Colorado State University. Libraries, 2023)
College mental health symptomatology is highly prevalent on college campuses across the nation. College student-athletes experience mental health issues at similar rates to their non-athlete peers. However, most colleges and universities do not have formal plans to address their student-athletes' mental health concerns. Considering the heterogeneity in experiences with mental health issues like anxiety and depression, applying person-centered analyses may help discern unidentified subgroups of student-athletes at greater risk of negative outcomes. The present study used latent class analysis to discern unidentified subgroups of student-athletes mental health symptoms and determine whether subgroups were associated with varying rates of help-seeking behaviors, health risk behaviors, and performance-related outcomes. Results indicated that a five-class model best fit the data, and that this model did not fit equally well for a comparative sample of non-student-athletes. Patterns of symptom endorsement within these classes ranged from high endorsement of all symptoms within the past month, to recent endorsement of feeling overwhelmed and exhausted, to no current or past-year mental health symptoms. Subsequent auxiliary testing identified classes of mental health symptoms associated with higher likelihood of engagement in health-risk behaviors and issues that could affect athletic performance. This study represented the first effort to discern latent subgroups of student-athletes characterized by varying experiences with mental health symptoms. Findings from the present study can help identify at-risk student-athletes in need of mental health support to attenuate symptom distress and mitigate negative consequences associated with these concerns. Further, athletic departments can use these findings to integrate simple mental health screening tools already circulating at schools across the nation to better support their student-athletes' mental health concerns. Potential application of these screening tools and treatment planning options are discussed.
Keywords: mental health; person-centered; college sports; student-athlete; mental health symptoms